“Be I a devil, yet God may pity me”: Rereading Marlowe’s The Tragical History of Doctor Faustus from Islamic Perspective - Ahmed, Mohammad Kaosar (International Journal of English Literature and Social Sciences (IJELS), 2019)
Marlowe’s Doctor Faustus has kept on catching the consideration of modern and postmodern pundits. For a very long while Faustian commentators are isolated between those two who see the play reflecting intense and steady religious standpoint, and the individuals who see the play as antireligious. This sharp resistance between the standard and heterodox perspectives partially mirrors the clashed life of the writer himself, who started his concise adulthood as a philosophy student and finished it as a famous figure blamed for agnosticism. This paper holds the perspective of the prior gathering of commentators contending that the concentration of deciphering this play ought to be religious. This article will endeavor to dissect the play from the perspective of Islam. Islam has something critical to say in regards to human nafs (mind), the everlasting clash between good and evil; friendship, and repentance and salvation.